Extended states in disordered doped polyacetylene chains - Lavarda, Francisco Carlos [UNESP]; Galvão, D. S.; Laks, B. (Elsevier, 1992)
In this work we study the electronic structure of ordered and disordered distributions of soliton-type defects along large, finite chains of trans-polyacetylene (trans-PA), as a function of the concentration of defects. The Negative Factor Counting method was used in a tight-binding parameterization with the geometrical data from Austin Method 1 calculations. Our results show the presence of extended (conducting) states at the Fermi level that could explain the semiconductor-metal transition for highly doped trans-polyacetylene, in accordance with the experimentally observed infrared-active vibrational states. © 1992.
Keywords: Conductive plastics; Crystal defects; Crystal structure; Electronic properties; Physical chemistry; Solid state physics; Doped trans polyacetylene; Electronic structure; Extended states; Negative factor counting method; Soliton type defects; Vibrational states; Polyacetylenes